Antifungal activity and toxicity of an octyl gallate-loaded nanostructured lipid system on cells and nonmammalian animals - Singulani, Junya L [UNESP]; Scorzoni, Liliana [UNESP]; Da Silva, Patricia B [UNESP]; Nazaré, Ana C [UNESP]; Polaquini, Carlos R [UNESP]; Baveloni, Franciele G [UNESP]; Chorilli, Marlus [UNESP]; Regasini, Luis O [UNESP]; Fusco-Almeida, Ana M [UNESP]; Mendes-Giannini, Maria J.S. [UNESP] (Taylor & Francis, 2022)
Aim: Octyl gallate (OG) loaded into a nanostructured lipid system (NLS) was tested for antifungal activity and in vitro and in vivo toxicity. Methods & Results: The features of NLS-OG were analyzed by dynamic light scattering and showed adequate size (132.1 nm) and homogeneity (polydispersity index = 0.200). OG was active against Paraccoccidioides spp., and NLS-OG did not affect antifungal activity. NLS-OG demonstrated reduced toxicity to lung cells and zebrafish embryos compared with OG, whereas NLS was toxic to hepatic cells. OG and NLS-OG did not show toxicity in a Galleria mellonella model at 20 mg/kg. All toxic concentrations were superior to MIC (antifungal activity). Conclusion: These results indicate good anti-Paracoccidioides activity and low toxicity of NLS-OG.
Keywords: antifungal activity; nanoparticles; nonconventional animal models; systemic mycosis; toxicity